2019
DOI: 10.1248/bpb.b19-00371
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of DDAH1 in the Activation of Spinal NOS Signaling in Early Stage of Mechanical Allodynia Induced by Exposure to Ischemic Stress in Mice

Abstract: The pathophysiological mechanism of central post-stroke pain (CPSP) is complicated and not well understood. Recently, it has been reported that an increase in the levels of spinal nitric oxide synthetase (NOS) occurs in cerebral ischemia, and spinal NOS is involved in the development of neuropathic pain. The aim of this study was to elucidate the mechanism of spinal NOS signaling in the development of CPSP. Male ddY mice were subjected to 30-min long bilateral carotid artery occlusion (BCAO). The withdrawal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…One possibility is that primary thalamic damage can cause retrograde axonal degeneration of the STT projecting fiber terminals, resulting in secondary spinal STT neuronal cell body death and neuroinflammation. Some previous reports support our presumption: (1) diffuse tensor tractography (DTT) showed likely damage of STT fibers after CPSP (Jang et al, 2019;Park et al, 2021); (2) involvement of spinal NOS signal in the development of bilateral carotid artery occlusion induced CPSP (Matsuura et al, 2019); (3) blockade of peripheral sensory input resulted in amelioration of CPSP (Haroutounian et al, 2018;Choi et al, 2021b). To address the above question, this study was designed to examine whether secondary neuronal death and neuroinflammation occur in the spinal dorsal horn after an establishment of the THS-induced pain hypersensitivity in rats, and if any, whether i.t.…”
Section: Introductionsupporting
confidence: 81%
“…One possibility is that primary thalamic damage can cause retrograde axonal degeneration of the STT projecting fiber terminals, resulting in secondary spinal STT neuronal cell body death and neuroinflammation. Some previous reports support our presumption: (1) diffuse tensor tractography (DTT) showed likely damage of STT fibers after CPSP (Jang et al, 2019;Park et al, 2021); (2) involvement of spinal NOS signal in the development of bilateral carotid artery occlusion induced CPSP (Matsuura et al, 2019); (3) blockade of peripheral sensory input resulted in amelioration of CPSP (Haroutounian et al, 2018;Choi et al, 2021b). To address the above question, this study was designed to examine whether secondary neuronal death and neuroinflammation occur in the spinal dorsal horn after an establishment of the THS-induced pain hypersensitivity in rats, and if any, whether i.t.…”
Section: Introductionsupporting
confidence: 81%
“… 18 Increased expression of spinal HMGB1 and the enzyme protein N(G), N(G)-Dimethylarginine dimethylaminohydrolase 1 (DDAH1), which regulates NOS signaling, in a post-ischemic stroke pain model resulted in bilateral carotid artery occlusion (BCAO). 17 , 19 HMGB1 is a non-histone nuclear protein that plays a critical role in regulating gene transcription. It can aggravate inflammation and pain via the TLR4 or RAGE signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated DDAH1 may be involved in CPSP occurrence by enhancing NO signaling. 19 A proteomic study of the spinal cord and DRG of mice with BCAO revealed that DDAH1 was involved and that its levels were altered, suggesting the role of NOS signaling in the inflammatory response at spinal cord after a stroke. 20 Anterograde, retrograde, and trans-synaptic degeneration may occur after nerve fiber injury.…”
Section: Resultsmentioning
confidence: 99%